Canalis sinuosus approximation on an impacted maxillary canine: a case report - Fahri Reza Ramadhan; Dwi Putri Wulansari; Lusi Epsilawati (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: This case report is aimed to report the finding of canalis sinuosus on an impacted maxillary canine using cone beam computed tomography (CBCT) examination. Case Report: A 21-year-old male was referred from orthodontic department to radiology department UNPAD Dental Hospital for CBCT to determine the treatment of malalignment asymptomatic maxillary canine. The case revealed the presence of canalis that was identified as a canalis sinuosus, a branch of the anterior superior alveolar nerve that rarely known by a practitioner, at the apex of impacted right maxillary canine. Conclusion: The information of this anatomical variation is important for professionals due to damage that may be caused during treatment. The use of advanced imaging examination is recommended to acknowledge the individual anatomical variation before determining the proper treatment planning.